The effect of compensation and work motivation on the productivity of public works and spatial planning employees in Morowali District - Mohammad Ega Nugraha; Armawati Armawati; Erwan Sastrawan Farid; Asbal Rasyid (Institute of Computer Science (IOCS), 2022)
Organizational success depends on the work productivity of human resources in achieving organizational goals. Human resources have an important role depending on the success or failure of the organization. Productive human resources if they have high work productivity and can achieve the goals or targets that have been set. One that affects employee work productivity is sensors, which is a very complex matter for employees, because compensation is a measure of the work done. Furthermore, work motivation, an employee will be considered valuable when the employee is trying to work to achieve targets and goals, then employees will work optimally by doing the job with the best results. The research objective was to determine the Effect of Compensation and Work Motivation on Employee Productivity. The sample of this research was all employees at the Office of Public Works and Spatial Planning, Morowali Regency, with a total of 57 employees. The research method used is quantitative, and multiple linear regression using the SPSS 23 application. The results show that the variables of Compensation and Work Motivation simultaneously significantly influence Employee productivity, the Compensation variable partially significantly influences Employee productivity, and the Work Motivation variable partially has a significant effect on employee productivity at the Public Works and Spatial Planning Office of Morowali Regency.